Daya Saing dan Potensi Ekspor Melati Putih Segar (Jasminum sambaac) Indonesia - Liska Simamora; Hendrik Johannes Nadapdap (JURNAL AGRICA, 2021)
The Indonesian Ministry of Agriculture is working to increase exports of Indonesian white jasmine flowers. These efforts will be realized more quickly if the competitiveness and development potential of commodity in various export destination countries are known. Therefore, this study aims to determine the competitiveness and development potential of white jasmine flower exports. The data used is the 2010-2019 time series data sourced from UN-COMTRADE and the trade map. The data were analyzed by using RCA to determine the competitiveness of commodities, followed by EPD to determine the position of the commodity market and the last stage with the X-model analysis to determine the potential for export development. The results show that the competitiveness of Indonesian white jasmine flowers is strong in China, Japan, Australia, Vietnam, Singapore and the United States and that Indonesian white jasmine flowers have potential in the optimistic category in Australia, Vietnam and Singapore and potential in China, Japan, Netherlands, United Kingdom and United States. This optimistic and potential market potential can be seized by Indonesia by striving for the quality of white jasmine flowers in accordance with the demands of export destination countries.